Tēcapaktar mūvar - Irāmaliṅkam Piḷḷai, Ve., 1888-1972 (SAMP early 20th-century Indian books project ;, 1953)
Life sketches of V.U. Chidambaram Pillai, 1872-1936, S. Satyamurti, 1887-1943, and M.P. Sivagnanam, b. 1906, Indian statesmen and freedom fighters.